2012
DOI: 10.4236/as.2012.34070
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic potential of <i>Artemisia biennis</i> (biennial wormwood)

Abstract: In this study, <i>Artemisia biennis</i> was seeded in a greenhouse and raised to an average plant height of 100 cm. Aboveground plant portions were harvested and partitioned into leaves and stems, and dried; while roots were either removed from some soil (soil – roots) or left in soil (soil + roots). Greenhouse studies were conducted to evaluate the allelopathic potential of <i>A. biennis</i> leaves, roots, and stems; and soil – roots, and soil + roots on <i>Solanum melanocerasum&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The lowest germination percentages (< 10%) were recorded when barley seeds were treated with 2.5-3.5 % of A. annua water extract (Fig 1). Allelopathic action of leaf tissues and extract fractions were previously reported in A. annua and other Artemisia species ( Passim and Rodrigues, 1999;Delabays et al, 2008;Panamanik et al, 2008;Kegode et al, 2012;Jessing et al, 2014). The observed reduction in barley germination under treatment of A. annua water extract could be attributed to the presence of water-soluble inhibitory allelochemicals.…”
Section: Resultsmentioning
confidence: 67%
“…The lowest germination percentages (< 10%) were recorded when barley seeds were treated with 2.5-3.5 % of A. annua water extract (Fig 1). Allelopathic action of leaf tissues and extract fractions were previously reported in A. annua and other Artemisia species ( Passim and Rodrigues, 1999;Delabays et al, 2008;Panamanik et al, 2008;Kegode et al, 2012;Jessing et al, 2014). The observed reduction in barley germination under treatment of A. annua water extract could be attributed to the presence of water-soluble inhibitory allelochemicals.…”
Section: Resultsmentioning
confidence: 67%
“…When competing with sunflower in southern Manitoba, A. biennis was found to reduce yields up to 46% when germinating at the same time as the crop in densities of about 800 plants m (2 (Lewis 2012). Part of the competitive effect from A. biennis is probably due to allelopathy (Kegode et al 2012) (see Section 7c). There are no reports of human or animal poisoning by A. biennis though milk can be tainted when it is eaten by dairy cows (Alex 1992).…”
Section: Description and Account Of Variationmentioning
confidence: 99%
“…However, once biologically active compounds have been isolated and characterized, they may not be phytotoxic to plants as was determined for arteminisin isolated from A. annua (Lydon et al 1997). The potential use of secondary phytotoxins produced by A. biennis for weed management has not been explored (Kegode et al 2012).…”
Section: Description and Account Of Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…The allelopathic properties are shown by plants of the genus Artemisia vulgaris L., which by colonization of the area, reduce diversity of the native flora [31]. The plant is a common weed [26], both in the fields and on roadsides or unused land [32]. Composition analyses of mugwort extracts have shown that they are rich in phenolic compounds, including chlorogenic acid derivatives, flavonoids, phenolic acid and ligands [33].…”
Section: Introductionmentioning
confidence: 99%